Interceptive orthodontic practices in general dentistry: a cross-sectional study - Currell Scott Derek; Vaughan Matthew; Dreyer Craig W. (Sciendo, 2019)
To evaluate the current practice of interceptive orthodontics undertaken by general dental practitioners and identify influencing factors.